INFLUENCE OF ORGANIZATIONAL CLIMATE AND COORDINATION ON THE PERFORMANCE OF RIAU PROVINCE GENERAL ELECTION COMMISSION EMPLOYEES - Yulistiafani Yulistiafani; Devi Deswimar (Yayasan Wayan Marwan Pulungan, 2024)
This research aims to determine the influence of organizational climate and coordination on employee performance. This research uses primary data obtained from respondents through questionnaires. The population in this study were employees who worked at the Riau Provincial General Election Commission office. The sample research method used the census method, while the analysis method used in this research was the multiple linear regression analysis method and was processed using the SPSS version 26 program application. The number of respondents in the sample in this study was 36 respondents. From the research results, it was found that the multiple linear regression analysis equation Y = 13,419 + 1,268 X1 + 0.923 research concludes that organizational climate and coordination simultaneously have a significant influence on employee performance at the Provincial General Election Commission with a calculated f value (51,201) > f table (3.27) and Sig. (0.00) < 0.05, this means Ha is accepted and Ho is rejected. Meanwhile, the value of R Square in the coefficient of determination (R2) is 0.756. This shows that the organizational climate and coordination variables as a whole have an influence of 75.6% on performance, while the remaining 24.4% is influenced by other variables not examined in this research.